2022
DOI: 10.1038/s41598-022-12319-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the pathogenicity of gut bacteria associated with tobacco caterpillar Spodoptera litura (Fab.)

Abstract: The symbiotic relationship between insects and gut microbes contributes to their fitness by serving immense range of functions viz. nutrition and digestion, detoxification, communication and reproduction etc. However, this relationship between insect and gut microbes varies from mutualistic to pathogenic. Gut microbes become pathogenic when the healthy normal microbial composition is perturbed leading to the death of insect host. Spodoptera litura (Fab.) is a polyphagous pest that causes significant damage to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This is indicated by LC50 values of 97.74 g and 70.32 g, respectively, while LC90, 147.60 g and 122.21 g, respectively, are suspected of causing test insects' death (Table 1). According to Zulfiana et al and Devi et al [6,24], B. thuringiensis given to S. litura larvae can cause mortality and increase mortality by 100% at 10 HSA doses of 30 g.mL -1. The mechanism of action of B. thuringiensis when entering the body of pests is to produce proteins that will interfere with/neutralize the digestive system of insects so that they cannot process food in the stomach.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…This is indicated by LC50 values of 97.74 g and 70.32 g, respectively, while LC90, 147.60 g and 122.21 g, respectively, are suspected of causing test insects' death (Table 1). According to Zulfiana et al and Devi et al [6,24], B. thuringiensis given to S. litura larvae can cause mortality and increase mortality by 100% at 10 HSA doses of 30 g.mL -1. The mechanism of action of B. thuringiensis when entering the body of pests is to produce proteins that will interfere with/neutralize the digestive system of insects so that they cannot process food in the stomach.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Microbial community analysis is a powerful tool in disease research [20]. In a previous similar study of the intestinal microbial community of insects, numerous microorganisms were found to live in the intestines of healthy insects, with the balance disrupted under specific environmental conditions, resulting in disease onset [21,22]. According to Koch's postulates, microbial community analysis is used in disease diagnosis because the initial condition of a disease-causing pathogen is "dominant" [23].…”
Section: Role Of Microbial Community In Inducing Sepsis In Silkwormsmentioning
confidence: 99%
“…However, there are associations in which they were reported to establish pathogenic interactions with lepidopteran host larvae [32][33][34]. In Spodoptera, Enterococcus faecalis has been shown pathogenic to Spodoptera exigua [35], and Enterococcus mundtii [36] and Enterococcus cloacae [37] to Spodoptera litura.…”
Section: Introductionmentioning
confidence: 99%